2022
DOI: 10.1039/d2fo00204c
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid ameliorates renal interstitial fibrosis by inhibiting the phosphorylated-AKT mediated epithelial–mesenchymal transition in vitro and in vivo

Abstract: Indoxyl sulfate (IS), a uremic toxin, causes chronic kidney disease (CKD) progression via renal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Administration of RA can reduce the expression levels of TGF-β1, type I collagen, vimentin, fibronectin, phosphorylated AKT (p-AKT), and α-SMA. This study implies that RA may offer a viable therapeutic agent in effectively managing renal interstitial fibrosis (23).…”
Section: Discussionmentioning
confidence: 78%
“…Administration of RA can reduce the expression levels of TGF-β1, type I collagen, vimentin, fibronectin, phosphorylated AKT (p-AKT), and α-SMA. This study implies that RA may offer a viable therapeutic agent in effectively managing renal interstitial fibrosis (23).…”
Section: Discussionmentioning
confidence: 78%
“…Studies have demonstrated that tripterine could decrease lung tissue injury by reducing capillary permeability, inhibiting inflammatory cytokines or chemokines, and governing the expression of numerous inflammatory mediators ( Law et al, 2011 ). The pathogenesis of PF is typically characterised by excessive extracellular matrix (ECM) deposition and EMT, during which several factors change, including excessive accumulation of type I and type III collagens, the main components of the ECM, and the up-regulation of mesenchymal markers, such as α -SMA and vimentin ( Hsieh et al, 2022 ). Through in vivo experiments, we reported that tripterine could decrease lung pathology and collagen deposition in the lung tissues of the model mice.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects of RA on kidney fibrosis and EMT were examined using a UUO mouse model and an indoxyl sulfate-stimulated NRK-52E cell model [75]. C57BL/6 mice were orally administered RA (10 or 20 mg kg −1 ) before and after UUO surgery.…”
Section: Kidney Fibrosismentioning
confidence: 99%